1986
DOI: 10.1111/j.1365-2621.1986.tb13950.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Content of Baked Sweet Potatoes from Different Cultivars and Lengths of Storage

Abstract: Sugar concentrations in baked roots of six different sweet potato (fpomoea batatas (L.) Lam.) cultivars were determined at harvest, after curing (32"C, 90% RH for 10 days), and during 46 wk of storage at 15.6"C. Maltose was the major sugar and sucrose the secondary sugar in all cultivars at harvest. Maltose decreased during curing and over long term storage. Sucrose, glucose, and fructose concentrations increased during curing and through at least 4 wk of storage in the orange-flesh cultivars. Sucrose concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 8 publications
(1 reference statement)
4
19
0
2
Order By: Relevance
“…The percent AIS of 400 or 600 Gy treated roots was lower than that for nonirradiated roots of both clones (P ≤ 0.05). The percent AIS of RY roots was higher than that reported for six cultivars (Picha, 1986). WP roots had similar percent AIS to that reported for 'Whitestar' (Picha, 1986).…”
Section: Resultssupporting
confidence: 58%
“…The percent AIS of 400 or 600 Gy treated roots was lower than that for nonirradiated roots of both clones (P ≤ 0.05). The percent AIS of RY roots was higher than that reported for six cultivars (Picha, 1986). WP roots had similar percent AIS to that reported for 'Whitestar' (Picha, 1986).…”
Section: Resultssupporting
confidence: 58%
“…In relation to the variation of these constituents, the antioxidant activity of sweet potatoes also shows similar variation during thermal processes [7]. Starch and sugar contents have also been reported to be changed by cooking procedures as starch decreases during the steaming process, yielding maltose [11].…”
Section: Introductionmentioning
confidence: 96%
“…Although the sugar composition of sweet potatoes mainly depends on the type of cultivar (Aina et al 2009), Koehler and Kays (1991) reported that the taste of baked sweet potatoes was mainly determined by their sugar content. Previous studies revealed that fresh sweet potatoes contained sucrose, glucose, and fructose (Picha 1986) but not maltose (Zhang et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Consumers enjoy the pleasant odor and flavor of baked sweet potatoes. Although chemical composition analysis of sweet potatoes has been previously documented (Ahmed et al 2010;Ahromrit and Nema 2010;Aina et al 2009;Picha 1985;Picha 1986;Vimala et al 2011), little information on the effect of baking has been reported (Lai et al 2011).…”
Section: Introductionmentioning
confidence: 99%